English Ecotourism Training in Tanjung Village, Pakis Aji, Jepara - Ahmad Saefudin; Aprilia Riyana Putri; Yushinta Eka Farida (Universitas Mathla'ul Anwar Banten, 2020)
In the industrial revolution 4.0 era, it is easier for people to communicate through social media such as Facebook, WhatsApp, Twitter and other similar applications. Similarly, in tracking tourist destinations. Tourists no longer need to laboriously search for information. With a device, everything is finished. Tanjung Village has beautiful ecotourism destinations such as Kali Bening, Jurang Nganten Waterfall, Kalen Wates Waterfall, and Kedung Plumpang. Geographical support in the form of mountainous areas adds a special attraction for visitors. Unfortunately, tourism management is still centralized based on the Village Government through the Tourism Awareness Group (Pokdarwis). In addition, tourism managers are also faced with the low Human Resources (HR) managers in receiving foreign tourists. The ability to communicate in English is still low. So, this dedication focuses on equipping the ability of natural tourism managers in Tanjung Village to communicate in English. They are equipped with basic English skills including general vocabulary of tourism (vocabulary), ways of speaking in English (speaking skills), and public speaking techniques of tour guides (Tour Guides). The final results of devotion produce English-Indonesian Tourism Pocket Dictionary products that can be utilized by managers of tourist destinations in welcoming foreign tourists.